An Efficient Method for Opening N-Tosylaziridines with Silylated Nucleophiles by Using Polystyrene-Supported 1,5,7-Triazabicyclo[4.4.0]dec-5-ene as a Reusable Organocatalyst - Matsukawa, Satoru; Tsukamoto, Kumiko; Yasuda, Shiori; Harada, Takeru (Synthesis, 2013)
Polystyrene-supported 1,5,7-triazabicyclo[4.4.0]dec-5-ene (PS-TBD) catalyzes the ring opening of N-tosylaziridines with trimethylsilyl cyanide, trimethylsilyl azide, or trimethylsilyl halides to give the corresponding products in high yields. PS-TBD can be easily recovered and reused without significant loss of catalytic activity.
Keywords: catalysis; polymers; ring opening; heterocycles; aziridines; sulfonamides